Directional current breaking capacity requirements for HVDC circuit breakers - Chaffey,G; Green,TC (IEEE, 2015)
Circuit breakers are expected to be a vital element within any high capacity HVDC network. This paper examines the directional current breaking capacity requirements that might be seen on a typical HVDC grid, as required for the specification of backup protection. It is shown that there is a significant difference between the peak prospective fault currents observed when the current direction is analysed. Several meshed network topologies are examined in order to evaluate and quantify the characteristics of the directional breaker requirement. Results are presented determining that both the current breaking magnitude duty and the time constraint typically associated with the DC fault are both significantly different when comparing the current direction through the breaker, which may influence future breaker design.